The Effectiveness of Religious Music and Digital Storytelling on the Level of Cooperativeness and Pain in Children During Invasive Treatment (Children’s Room, Zalecha Local Hospital, Martapura) - Iis Pusparina; Insana Maria; Raihana Norfitri (Universitas Airlangga, 2020)
Introduction: The impact of invasive treatment procedure in children undergoing healthcare in hospital is a trauma since the treatment brings about an uncomfortable feeling. The study aimed at factors in the application of atraumatic care in the form of religious music and digital storytelling given to patients. The study aims to find the difference of effectiveness between religious music and digital storytelling in regard to the level of cooperativeness and pain in children as they undergo invasive treatmentMethods: The design of research was quasi-experiment with time series design. There were two group treatments; the group of intervention 1 consisting of preschool children undergoing invasive treatment via religious music and the group of intervention 2 consisting of preschool children undergoing invasive treatment via digital storytelling.Results: The statistical test shows p: 1.000 > 0.05, meaning that there is no difference between religious music and storytelling in regard to the level of cooperativeness and pain in children having invasive treatmentConclusion: Religious music and digital storytelling have similar effectiveness of influence in regard to the change of cooperativeness and pain level in children having invasive treatment.